South of the Sahara, Africa. »Entangled Africa« – new interdisciplinary research from Africa’s east to west coast. December 2018 to December 2020 - Sigl, Johanna; Linstädter, Jörg (e-Forschungsberichte des DAI, 2021)
The history of northern hemispheric Africa between 6000 and 500 BP has been subject to many political, social and religious processes, to major climate and environmental events, to conflicts and migration. The archaeological research work in Africa often took an extra-African point of view on these events and factors, thus it still lacks understanding of inner-African processes. In the DFG-funded priority program »Entangled Africa« a fundamental change of perspective is attempted. The interdisciplinary research work is focusing on indicators, mechanisms and patters of interaction in sub-Saharan Africa from an inner-African point of view.